Acute pericarditis in an adult with cystic fibrosis: a case report and literature review - Amer Abu-Shanab; Muhammad Tayyeb; Muhammad Saad Anwar; David Angelo Aquino; Pierre Amog; Abdalhakim Shubietah; Doantrang Du (European Journal of Case Reports in Internal Medicine)
Introduction: Cystic fibrosis, an autosomal recessive disorder (1 in 3,000–6,000 births), causes thick mucus and recurrent lung infections. Improved survival has revealed rare complications such as constrictive pericarditis and cardiac tamponade. Case description: A 24-year-old female with cystic fibrosis, diagnosed at nine months, presented with two weeks of dyspnoea. Examination revealed bilateral rhonchi, facial oedema and non-pitting thigh oedema. Laboratory results showed a white blood cell count of 11.3 ×109/l, erythrocyte sedimentation rate of 99 mm/hr and C-reactive protein level of 45.3 mg/dl. Initially admitted for cystic fibrosis exacerbation, she was found to have pericardial effusion. Despite facial and lower extremity swelling, she denied cardiac symptoms. During hospitalisation, she developed haemodynamic instability requiring pericardiocentesis, with echocardiography confirming constrictive pericarditis. Chest computed tomography angiography showed pericardial calcifications; autoimmune workup was negative. She was discharged on colchicine with close follow-up. Conclusion: Clinicians should have a high index of suspicion for underlying cardiac complications in patients presenting with exacerbations of cystic fibrosis.